Postnatal Development of NPY and Somatostatin-28 Peptidergic Populations in the Human Angular Bundle - Cebada-Sánchez, Sandra; Marcos Rabal, Pilar; Insausti, Ana María; Insausti, Ricardo (Frontiers in Neuroanatomy, 2019)
The angular bundle is a white matter fiber fascicle, which runs longitudinally along the parahippocampal gyrus. It is best known for carrying fibers from the entorhinal cortex (EC) to the hippocampus through the perforant and alvear pathways, as well as for carrying hippocampal output to the neocortex, and distributing fibers to polysensory cortex. The angular bundle is already present prenatally at the beginning of the fetal period. Connections between the EC and the hippocampus are established by the 20th gestational week (gw). In the postnatal period, it shows increasing myelination. The angular bundle, as well as other white matter portions of gyral surfaces in the brain, presents interstitial neurons, a remnant of subplate neurons. Those interstitial neurons show neurochemical phenotypes both prenatally and postnatally, among which, neuropeptide Y (NPY) and Somatostatin-28 (SOM-28) peptidergic populations are noticeable, and accompany the fiber connections in the maturation of the hippocampal formation. We sought to investigate the topography of the postnatal distribution and relative density of neurons immunoreactive for NPY or SOM in the angular bundle along the rostrocaudal axis of the hippocampus. The study was carried out in 15 cases, ranging from 35 gws, up to 14 year old. All cases showed positive neurons showing a polygonal or spindle shaped morphology for both peptides, scattered throughout the angular bundle. The highest number of positive neurons appeared around birth and the ensuing weeks. Up to one and a half years, the density of both peptidergic populations decreased slightly. However, cases older than 2 years of age showed a substantial decrease in density of immunolabeled neurons, density that did not showed a minor decrease in density of positive neurons in cases older than 2 years. In addition, a topography from caudal to rostral levels of the angular bundle was detected at all ages. The functional significance of interstitial cells is unknown, but the existence of SOM and NPY peptidergic neurons, presumably inhibitory, in the white matter of the angular bundle, could contribute to the basic wiring of the hippocampal formation, through which autobiographical and spatial memories can begin to be stored in the infant brain.